Pengembangan Perangkat Pembelajaran Mengunakan Pendekatan Konstruktivisme Berbasis Karakter Materi Pada Mata Pelajaran Ekonomi Kelas X SMA PGRI 1 Di Kota Padang - Meri Rahmania; Sri Wahyun; Mona Amelia; Desi Areva (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2019)
Different innovations in education world especially in learning. appearEducation experts try to find a solution to improve the quality of education especially in learning in the classroom.One of the innovations is the approach based on characters matter. constructivismThe chosen this approach to learning make students more creative and active in learning for all persoalanya exists so that they wanted to try to solve this problem.The methodology used is learning. model of deviceAims to develop a device learning and learning outcomes assessment from the classroom. Learning based on the approach of constructivism character based, material covering four stages, which is (1) The stage of the perception, (2) The exploration, (3) The discussion and explanation concept, and (4) Developmental stage and applications concept. Based on four stages done at school there are several revisions done in lesson plans and teaching materials economic is concocted from various.  Key words: approach constructivism , material character